Early fluoride intake and Molar Incisor Hypomineralisation (MIH) defects: a systematic review and dose-response meta-analysis - Veneri, Federica; Filippini, Tommaso; Cecchini, Marta; Vinceti, Marco; Consolo, Ugo; Luigi Generali (Acta Biomedica Atenei Parmensis, 2024)
Background: Excessive intake of fluoride has been implicated in the complex multifactorial etiology of hypomineralisation (MIH) defects. Objective: To study the possible effect of early exposure to fluoride on the risk of molar incisor hypomineralisation, also through a dose-response approach. Methods: Observational and clinical studies investigating the relation between fluoride exposure from any source or evaluating exposure biomarkers and MIH defects. PubMed MEDLINE, Embase and Web of Science databases were consulted up to December 1, 2023, using terms related to “fluoride”, “enamel defects” and “demarcated opacities”. We performed a meta-analysis comparing the highest versus lowest fluoride exposure using a random-effects model, and we quantitively assessed this relation using piece-wise linear meta-regression. Results: Thirteen studies were included in the meta-analysis, 12 of which were eligible for the dose-response analysis, all regarding exposure from fluoride in drinking water. Three of them specifically addressed MIH, while the remaining concerned “demarcated opacities”, yet with features attributable to MIH. Comparing the highest versus lowest water fluoride exposure categories, virtually no evidence of a fluoride effect was identified, with an overall odds ratio of 0.93 [95% confidence interval 0.60; 1.45]. The dose-response meta-regression showed a decreasing risk for MIH defects exposure up to 1 mg/L, whereas an increase in risk emerged at higher exposure levels. Conclusions: This meta-analysis suggests that early systemic exposure to fluoride may affect the occurrence of MIH defects differently depending on fluoride concentration. However, these results need to be evaluated with caution due to potential methodological limitations of the studies included.